Efforts to Improve Children's Learning Skills Through Learning Guidance Activities - Febriani, Ari Ana; Stiawan, Dani; Primandoni, Ade Bagus; Muslim, Rachmat Imam; Sugiharto, Prasetyawan Aji (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
Education will encourage people to learn actively, independently, and empower all the potential that exists within the individual. One way to do this is by studying. Learning is a process of effort that is carried out by a person to obtain a new change in behavior as a whole, as a result of his own experience in interaction with his environment. To achieve changes in children, children need to have skills in learning where learning skills are a system, methods and techniques that are well mastered by students regarding knowledge material or learning material delivered by the teacher in an agile, effective and efficient manner. Improving learning skills for children in Jungsemi village is carried out through the Real Work Lecture (KKN) program. KKN is an intracurricular activity that combines the implementation of the Tri Dharma of higher education, namely education, research, and community service. Activities in the field of education carried out are tutoring activities where the material being guided is Mathematics, English and Skills with the target being elementary school children in Jungsemi village. This tutoring activity aims to fill in positive activities during winter break.